Targeting Alpha-Amylase: Discovering Novel Inhibitors through E-Pharmacophore Modeling and in vitro studies - Al-Zahrani, Norah Saeed; El-Gamal, Basiouny; Ellatif, Mohamed Abd; Elrouf, Mohamed Babiker Abd; Musa, Alam Eldin Musa Mustafa; Ali, Niemat Mohammed Tahir; Ahsan, Marya; Mallick, Ayaz Khurram; Patel, Ayyub Ali; Omer, Safaa; Mohieldeen, Muniera; Mohamed, Hagar Mohamed; et al. (Indian Journal of Pharmaceutical Education and Research, 2018)
Background: Diabetes mellitus is a metabolic disorder affecting millions worldwide, with prevalence continuing to rise globally. A major therapeutic challenge is controlling postprandial blood glucose spikes that contribute to chronic hyperglycemia and associated vascular complications in diabetes. Pancreatic alpha-amylase is a key enzyme responsible for digesting dietary carbohydrates into absorbable sugars, making it an attractive target for managing postprandial hyperglycemia. While inhibitors like acarbose are available, side effects limit their use. Structure-guided drug design can reveal improved candidates. Materials and Methods: The X-ray structure of acarbose-bound alpha-amylase guided pharmacophore modeling to encode critical chemical features for inhibition. Database screening retrieved compounds matching this bioactive geometry. Top hits through pharmacophore modeling were evaluated through molecular docking versus co-crystallized references. Results: A validated 7-feature pharmacophore model captured essential hydrogen bonding and shape complementarity constraints within the enzyme active site. Screening retrieved distinct chemotypes scored well on pharmacophoric fit and strain energy. Molecular docking confirmed the top hit CID70684192 having strong predicted affinity (binding energy -7.1 kcal/mol) through conserved polar contacts and shape complementarity. In in vitro studies, CID: 70684192 showed no significant effect on the viability of AR4-2J pancreatic cells at various concentrations and exposure times. However, treatment of rat AR42J pancreatic cells with IC50 concentration CID: 70684192 (7 nM) significantly decreased alpha-amylase activity in treated cells compared to control. Conclusion: An integrated in silico and in vitro approach discovered novel alpha-amylase inhibitors with robust computational evidence of improved predicted activity over existing drugs. These represent promising candidates for experimental testing to reveal better tolerated therapies aiding diabetes management and postprandial glucose control. Structure-guided design enabled rapid identification of bioactive small molecules from chemical space.
Keywords: Acarbose; Alpha-Amylase; Database Screening; Diabetes mellitus; E-pharmacophore; Voglibose